Building the Bronze Age : architectural and social change on the Greek mainland during Early Helladic III, Middle Helladic and Late Helladic I - Wiersma, Corien, 1983- (Archaeopress, 2014)
Wiersma analyses Early Helladic III, Middle Helladic and Late Helladic I domestic architecture with reference to social organization and social change. This book covers domestic architecture from the southern and central Greek mainland up to southern Thessaly.